Effect of subsequent Hot Isostatic Pressing on mechanical properties of ASTM F75 alloy produced by Selective Laser Melting. (July 2015) - Haan, J.; Asseln, M.; Zivcec, M.; Eschweiler, J.; Radermacher, R.; Broeckmann, C.
<x content-type="archive" xml:space="preserve">Abstract</x> The Co-based alloy ASTM (Co – 28.5 wt.-% Cr – 6.3 wt.-% Mo) is widely used for medical implants, e.g. knee prostheses, and is commonly processed by investment casting. Selective laser (SLM) melting is supposed to be an efficient alternative for the production of individually designed knee implants regarding production time and production costs. The mechanical properties, in particular the fatigue strength, of the material have been studied in different states of the material. The mechanical properties of investment casted ASTM F75 and PM-SLM produced ASTM F75 were investigated. The focus in this study was on the PM-SLM material, the specimens were initially produced by selective laser melting and a part of the specimens were further processed by hot isostatic pressing (HIP). The PM-SLM material was mechanically tested in the as-SLM state as well as in the SLM+HIP state. It was found that the mechanical properties of the as-SLM material did not reach the level of the fatigue strength of as cast material. The post-densification treatment by HIP offers distinct improvements regarding the fatigue strength compared to the as-SLM material.